VALUASI EKONOMI OBJEK WISATA GOA GONG DI KABUPATEN PACITAN: TRAVEL COST METHOD DAN CONTINGENT VALUATION METHOD - , Yeni Lisiana Putri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to identify what kind of factor that influences the number of tourists visit and also to estimate the economic value of Gong Cave, in Pacitan Regency. The valuation of tourism object in Gong Cave is an application of Travel Cost Method and Contingent Valuation Method using count data models and ordinary least square as an analysis tools. Sample used in this study is about 60 respondents. The factors which affect the number of visit in Gong Cave based on travel cost method are travel cost, income, and time. While, the factors which affect willingness to pay based on contingent valuation method are income, availability of information, and quality. Economic value of Gong Cave based on travel cost method are about Rp79.058.000.000,00 until Rp197.700.000.000,00, with the mean value is Rp138.379.000.000,00, while, the economic value of Gong Cave based on contingent valuation method are about Rp3.000.000.000,00 until Rp5.900.000.000,00 with the average mean is Rp4.700.000.000,00.